International versus domestic entrepreneurship: New venture strategic behavior and industry structure - McDougall, Patricia P. (Journal of Business Venturing, 1989)
International entrepreneurship is defined in this study as the development of international new ventures or start-ups that, from their inception, engage in international business, thus viewing their operating domain as international from the initial stages of the firm's operation. One hundred and eighty-eight new venture firms in the computer and communications equipment manufacturing industries are classified according to the percentage of their sales in the international market. Ventures with no sales derived from international activities are considered “domestic” new ventures, and ventures with sales from international activities comprising greater than 5% of total sales are considered “international” new ventures. The strategy and industry structure profiles of international new ventures are significantly different from domestic new ventures. The internationals pursue much broader market-based strategies, seeking a strategy of broad market coverage through developing and controlling numerous distribution channels, serving numerous customers in diverse market segments, and developing high market or product visibility. The internationals also emphasize a more aggressive entry strategy, building on outside financial and production resources to enter numerous geographical markets on a large scale. Securing patent technology is also an important component of their strategy. This suggests that the internationals compete by entering the industry on a large scale, seeking to penetrate multiple markets, with the recognition that external resources are necessary to support such an entry. Whereas both the domestics and the internationals characterize domestic competition as being relatively intense, the international new ventures compete in industries with higher levels of international competition. It is not clear from this research whether the new venture selects an industry with a high degree of international competition and therefore responds with an international orientation or, because the new venture has an international orientation, it perceives or recognizes a higher degree of international competition. Another industry structure difference is the internationals' perceived higher degree of restrictiveness due to government regulation. It is unclear whether this restrictiveness motivates new ventures to seek less-regulated international environments or if it indicates that when competing internationally, the new venture is confronted with increased regulatory requirements. Domestic new ventures are distinguished by their emphasis on a production expansion strategy and customer specialization strategy. The production specialization strategy consists of focusing on limited geographical markets, maintaining excess capacity, and pursuing forward integration. The customer specialization strategy incorporates the production of a specialty product that is purchased infrequently. Thus, for both of the domestic strategies, a consistent “closeness” between the producer and consumer is implied. This may be an important basis underlining the new venture's decision to compete in an exclusive domestic context. This study offers initial support for the notion of international entrepreneurship by its findings that there are significant differences between new venture firms competing domestically and new ventures choosing to also enter international markets.